2004
DOI: 10.1108/13673270410541042
|View full text |Cite
|
Sign up to set email alerts
|

Informal network players, knowledge integration, and competitive advantage

Abstract: In today's hyper-competitive environments, generation and dissipation of knowledge can no longer be understood from within the boundaries of formal organizational mechanisms. Previously, researchers have studied knowledge management based on formal mechanisms; however, few have examined the role played by informal mechanisms. In this paper, we examine the roles of informal network players in knowledge integration and discuss their effects on competitive advantage. For researchers, our paper provides testable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 21 publications
(19 reference statements)
2
34
0
6
Order By: Relevance
“…Interestingly, it should be noted that while most of the studies focus on the sensemaking concept as a portrait of the ‘organizing’ in the team context (Ashmos and Nathan, ; Klein et al., ), a few studies mention about it as a specific capability (Weick et al., ). Awazu (), for instance, notes that sensemaking is an important capability for organizations and groups because it integrates people's thoughts and generates new knowledge as well as constituting an ability to reconfigure existent knowledge to solve current problems. Nevertheless, we know less about how to conceptualize and then operationalize the team sensemaking capability in the technology innovation management (TIM) literature.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it should be noted that while most of the studies focus on the sensemaking concept as a portrait of the ‘organizing’ in the team context (Ashmos and Nathan, ; Klein et al., ), a few studies mention about it as a specific capability (Weick et al., ). Awazu (), for instance, notes that sensemaking is an important capability for organizations and groups because it integrates people's thoughts and generates new knowledge as well as constituting an ability to reconfigure existent knowledge to solve current problems. Nevertheless, we know less about how to conceptualize and then operationalize the team sensemaking capability in the technology innovation management (TIM) literature.…”
Section: Introductionmentioning
confidence: 99%
“…This need is also confirmed in this research. The scientific literature provides evidence of the correlation of informal knowledge sharing and the operation of informal networks that explains the natural existence of workplace gossip (Awazu, 2004;Bresnen, 2003) (as cited in Wabwezi, 2011, p. 16). Further research has also confirmed the relevance of knowledge sharing and its occurrence in the form of gossip in practice, which is also proved by this research.…”
Section: Discussionmentioning
confidence: 99%
“…Innovation networks are an important avenues by which different enterprises can go beyond their organizational boundaries to acquire external technology and innovation resources (Freeman, 1991). Awazu (2004) showed that companies can gain comparative advantages by integrating online knowledge. Recently, firms have been going beyond their boundaries to foster learning activities at both the inter-firm and inter-industry levels and on both the national and international scale (Alguezaui and Filieri, 2010).…”
Section: Global Network Positionmentioning
confidence: 99%